Exosome α-Synuclein Release in Plasma May be Associated With Postoperative Delirium in Hip Fracture Patients - Yuan, Yi; Li, Zhengqian; Yang, Ning; Han, Yongzheng; Ji, Xiaojuan; Han, Dengyang; Wang, Xiaoxiao; Li, Yue; Liu, Taotao; Yuan, Feng; He, Jindan; Liu, Yajie; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Little is known about the underlying mechanisms of the similarities in the core features of postoperative delirium (POD) and Alpha-synuclein (α-syn)-related cognitive disorders. We herein investigated associations between fluctuated levels of exosomal α-syn in the plasma and POD presentation in geriatric hip fracture patients. Methods: We conducted an observational, prospective, and 1:1 matched (on age older than 65, hip fracture diagnosis, American Society of Anesthesiologists’ physical status, duration of surgery, and intraoperative bleeding) case-control study: POD cases and non-POD controls were selected from the overall cohort by using Confusion Assessment Method. Delirium severity was measured by Memorial Delirium Assessment Scale (MDAS). Plasma exosome levels of α-syn were examined preoperatively and at the time that POD was diagnosed, by using an established immunocapture technology based on a putative brain-cell-specific marker. Circulating concentrations of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) were also determined. The relationship between α-syn levels and POD risk, as well as the association between α-syn and MDAS scores and plasma cytokines were assessed. Results: POD incidence was 8.4% (17/202). Postoperative α-syn were either elevated or lowered. As primary outcome variables, the change of α-syn in POD patients was significantly higher than non-POD ones (21.0 ± 29.3 pg.ml-1 vs.1.9 ± 20.0, P = 0.047). The α-syn alteration was positively correlated to MDAS (r = 0.436，P = 0.010) and the change of IL-6 (r = 0.383，P = 0.025). Conclusions: Exosome α-syn release in plasma may be associated with the POD development which might be due to systemic inflammation.